1986
DOI: 10.1007/bf00422739
|View full text |Cite
|
Sign up to set email alerts
|

Endurance capacity of untrained males and females in isometric and dynamic muscular contractions

Abstract: The capacity to perform isometric and dynamic muscle contractions at different forces has been measured in two separate groups of subjects: 25 men and 25 women performed sustained isometric contractions of the knee-extensor muscles of their stronger leg to fatigue, at forces corresponding to 80%, 50% and 20% of the maximum voluntary force of contraction (MVC). The second experimental model involved a bilateral elbow-flexion weight lifting exercise. Eleven women and 12 men performed repetitions at loads corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
148
8
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(176 citation statements)
references
References 20 publications
19
148
8
1
Order By: Relevance
“…This increase in unsteadiness has been reported in the upper extremity both during as well as after sustained contractions (Maughan et al 1986;Huang et al 2006;Contessa et al 2009) and after repetitive fatiguing tasks (Dartnall et al 2008;Dundon et al 2008). However, except for a few studies on fatigue during sustained contractions (Maughan et al 1986;Clark et al 2005), the relationship between fatigue and unsteadiness in the lower extremity, and therefore during functional activities, remains uninvestigated.…”
Section: Introductionmentioning
confidence: 87%
“…This increase in unsteadiness has been reported in the upper extremity both during as well as after sustained contractions (Maughan et al 1986;Huang et al 2006;Contessa et al 2009) and after repetitive fatiguing tasks (Dartnall et al 2008;Dundon et al 2008). However, except for a few studies on fatigue during sustained contractions (Maughan et al 1986;Clark et al 2005), the relationship between fatigue and unsteadiness in the lower extremity, and therefore during functional activities, remains uninvestigated.…”
Section: Introductionmentioning
confidence: 87%
“…Similarly to our findings during short duration and ramp 13 contractions, the control mechanisms influencing the amount and structure of force 14 variability could be gender dependent. 15 Moreover, the lower complexity or higher predictability found in females compared with 16 males corresponding to a higher degree of regularity may not be favourable. Indeed, it 17 may not allow appropriate adaptation to changes in sensory afferent feedback and may In summary, the analysis variability of task-related and tangential forces showed that the 1 changes in the amount and structure of force variability differed with increasing 2 contraction level and increased similarly with contraction time.…”
mentioning
confidence: 99%
“…This time approximately agreed with peak force time (79.0 s) in males. Maughan et al (1986) reported that muscle endurance was higher in females in loads below 70% MVC, but there is not a gender difference in loads above 80% MVC. Laforest et al (1990) reported that there were not gender differences in force values during maximal work.…”
Section: Discussionmentioning
confidence: 93%
“…Also, the differences among individuals (Yamaji et al 2002;Yamaji et al 2004) and between genders (Maughan et al 1986;Laforest et al 1990) increase during a large decrease in force, until reaching a steady state. However, because measurement of muscle endurance using a progressive workload is without precedent, the effect of decreasing force is not entirely clear.…”
Section: Setting Of Progressive Workloads and Measurement Timementioning
confidence: 99%
See 1 more Smart Citation